ANALISIS PENGARUH UPAH MINIMUM DAN INFLASI TERHADAP KESEMPATAN KERJA SEKTOR INDUSTRI PENGOLAHAN BESAR DAN SEDANG DI JAWA TENGAH (35 KAB/KOTA) - Hutagalung, Paul SP; Santosa, Purbayu Budi (Diponegoro Journal of Economics, 2013)
The research aims to determine how much the influence about minimum wage and inflation to the large and medium manufacturing industries in central java (35 districts / cities). The analytical method in this research is Ordinary Least Square, where Y refers to variable of job opportunities, X1 refers to minimum wage and X2 refers to inflation. The research showed that the determinant coefficient (R2) of 0,161 which means that employmentâ€™s variation is affected by in the independent variable is equal to 16,1%. Based on the Partial Test, minimum wage were significantly influence to the employment opportunities which seen from the probability value of 0,000 and using degree of trust in amount of 0,05 with F-statistic equal of 4,637 and it means that if minimum wage rised, so the employment opportunities in the district / town in Central Java increased. Variable inflation did not affect the employment opportunities seen from profitabistas value more than 0,05 is equal to 0,463 for inflation. Moreover, T-statistic in the amount of 0,753 was smaller than T table that indicates the alternative hypothesis was rejected. Based on Simultaneous Test (statistic F test) obtained F-statistic value in the amount of 10,963 and sig = 0.000 <5%. ThisÂ  means, independent variable (minimum wage and inflation) affected dependent variable.